Differences Use of Yoga and Self-Tapping Towards Long Pain of Primary Dysmenorrhea on Adolescent - Mar’atun Ulaa; Wiwin Lismidiati; Elsi Dwi Hapsari (IJNP (Indonesian Journal of Nursing Practices), 2017)
Background: Dysmenorrhea is a common complaint in young women, characterized by pain. Dysmenorrhea pain has a significant impact on women's lives, such as limitations in daily activities. Primary dysmenorrhea can be treated using yoga and self-tapping. Objective: understanding differences on use of Complementary and Alternative Medicine (CAM), such as yoga and self-tapping towards changing long pain of primary dysmenorrheal.  Method: Study was conducted by quasi experiment with nonequivalent pretest-posttest control group design. Study was conducted on November 2016 until February2017 in SMK “A” Pedan Klaten and SMK “B” Klaten. Sample of study amounted 88 respondent divided on 47 respondents on experimental group and 41 respondent as control group. The experimental group was given a yoga intervention; control group was given self-tapping. Measuring tool using Numerical Rating Scale (NRS). Data analysis using t-test for independent sample, Mann-Whitney test and Wilcoxon.Result: Statistically yoga and self-tapping were equally effective in reducing the long pain of primary dysmenorrheal with p values of 0.000 and 0.012 respectively. Clinically yoga is more effective in reducing the long pain of primary dysmenorrhea with mean 1,49 compared with self-tapping 0,46.Conclusion: Yoga become more effective intervention on reduction long pain of primary dysmenorrhea compared to self-tapping.